Estudantes em Angra, mão-de-obra dos reis... : a política pública municipal para a educação de jovens e adultos de Angra dos Reis no período 2000-2004 - Cardoso, Marcio Plastina (2006)
This work intends to recover and probe the Regular Night shift teaching Project at Cacique Cunhãbebe School in Angra dos Reis, Rio de Janeiro, from 2000 to 2004. It focuses to research internally and externally the formulation and implementation of its political and educational Young and Adult modality project. It takes into account to investigate the reasons that took this project, made collectively and based on the Secretaria Municipal de Educação curriculum standard, dating the last three consecutive periods of govern of the Partido dos Trabalhadores (PT 1989-2000) to an abandoned situation and an imposition of a new project in 2001. Thus, it tries to analyse the relationship between the actors involved in the construction and implementation of the project itself to the one established between those who defended it and those who imposed it to an abandon. To do so, it intends to analyse the route of the current project as a starting point to a wider movement leading to a general understanding of the public educational politics of the Young and Adult Student in Angra dos Reis during the period of 2000 / 2004.